MANAJEMEN PEMBELAJARAN DI SEKOLAH DASAR NEGERI 4 KECAMATAN BAOLAN KABUPATEN TOLITOLI - Fatmawati, Andi (Eklektika: Jurnal Pemikiran dan Penelitian Administrasi Pendidikan, 2017)
Learning is an integral part of the educational process. A good or quality learning process determines the realization of educational goals. The objectives of this research are: To investigate the implementation of learning management that focuses on four problems: (1) learning planning, (2) learning strategies, (3) evaluation of learning, and (4) supporting factors and obstacles in learning at Tolitoli SDN 4. The results showed: (a) Learning management was carried out through four stages: planning stage, strategy stage, evaluation stage and supporting and inhibiting factors. In each stage. The main stage of the implementation is oriented to the quality of learning in an inspiring, fun, challenging, motivating students to actively participate, as well as providing sufficient space for initiative, creativity, and independence, (b) Efforts made by the teacher to improve the quality of learning, (c) Supporting factors for the management of learning quality improvement are: parental support for learning facilities and the principal's leadership model, (d) As for what is problematic among others, the assumption that learning is difficult and student motivation is lacking.